The Influence of Islamic Capital Structure, Governance on Risk and Soundness of Sharia Banking - Oktaviansyah, Hendrik Tri; Arif, Alfi; Asfufi, Nanang (VALUE: Journal of Business Studies, 2024)
Objective: This study aims to determine the effect of capital structure, governance on the risk and soundness of Islamic banking. Methodology: This research is a quantitative research. The sample in this study was 10 Islamic banking institutions in Indonesia which were analyzed for 10 years from 2011-2020 while the data used in this study were primary data and secondary data. The primary data used in this study was used by using a questionnaire in various management parties related to the health of Islamic Banks with the ANGELS approach. While the secondary data in the study is the data of Islamic banking financial statements for 10 years. Results: The results showed that the capital structure had a positive effect on the health of Islamic banks, while governance and risk had a significant positive effect on the health of Islamic banks. Originality: The originality of this research is an assessment of the health of Islamic banks measured using ANGELS this is because the CAMELS and RGEC methods have often been used by Islamic banks as an assessment of the health of Islamic banks. This research contributes to the importance of capital structure, governance and risk management for Islamic banks in Indonesia so that the health of Islamic banks improves.